2021
DOI: 10.3390/app11125699
|View full text |Cite
|
Sign up to set email alerts
|

Seamless Human–Robot Collaborative Assembly Using Artificial Intelligence and Wearable Devices

Abstract: Seamless human–robot collaboration requires the equipping of robots with cognitive capabilities that enable their awareness of the environment, as well as the actions that take place inside the assembly cell. This paper proposes an AI-based system comprised of three modules that can capture the operator and environment status and process status, identify the tasks that are being executed by the operator using vision-based machine learning, and provide customized operator support from the robot side for shared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 24 publications
0
36
0
Order By: Relevance
“…Figure 2 shows the number of articles per country. Our results allow us to say that the country where more studies have been developed in this field is Italy [1,12,[27][28][29][30][31][32][33], followed by the USA [8,34], United Kingdom [18,35], France [11,31], and Greece [22,36]. In the rest of the countries, only one study per country was found.…”
Section: Resultsmentioning
confidence: 64%
See 4 more Smart Citations
“…Figure 2 shows the number of articles per country. Our results allow us to say that the country where more studies have been developed in this field is Italy [1,12,[27][28][29][30][31][32][33], followed by the USA [8,34], United Kingdom [18,35], France [11,31], and Greece [22,36]. In the rest of the countries, only one study per country was found.…”
Section: Resultsmentioning
confidence: 64%
“…Regarding the year of publication, our study shows that the oldest paper presented in this review dates to 2013 [31] (Figure 3). Moreover, the largest number of studies found have been published in 2021 [11,12,19,22,27,32,33,37,38]. These two findings point ou that E&HF as a requirement in HRC systems is an emergent/recent research topic.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations